The Hidden Histories of War Crimes Trials - Simpson, Gerry J.; Heller, Kevin Jon (2013)
Several instances of war crimes trials are familiar to all scholars, but in order to advance understanding of the development of international criminal law, it is important to provide a full range of evidence from less-familiar trials. This book therefore provides a comprehensive overview, uncovering and exploring some of the lesser-known war crimes trials that have taken place in a variety of contexts: international and domestic, northern and southern, historic and contemporary. It analyses these trials with a view to recognizing institutional innovations, clarifying doctrinal debates, and identifying their general relevance to contemporary international criminal law. At the same time, the book recognizes international criminal law's history of suppression or sublimation: What stories has the discipline refused to tell? What stories have been displaced by the ones it has told? Has international criminal law's framing or telling of these stories excluded other possibilities? And — perhaps most important of all — how can recovering the lost stories and imagining new narrative forms reconfigure the discipline?...